Cellulases production on paper and sawdust using native Trichoderma asperellum - Y-Maritza Zapata, Angelica Galviz-Quezada, Víctor-Manuel Osorio-Echeverri (Pontificia Universidad Javeriana, 2018)
Microbial cellulases are industrially used enzymes that catalyze the cleavage of the glycosidic bonds of cellulose. This hydrolysis yields sugars that can be used in processes such as bioethanol production. These enzymes are mainly produced by fungi belonging to the genus Trichoderma via submerged or solid state fermentation with cellulosic materials as substrates. Recent publications have increasingly demonstrated that alternatives to T. reesei enzymes in the production of second-generation biofuels exist. Here, cellulolytic activities of crude extracts obtained from a native isolate of T. asperellum from coffe pulp and a strain of T. reesei were evaluated. Solid state fermentations were performed using paper and sawdust as substrates. The activities were measured after 12 days of incubation. The extracts obtained from T. reesei showed higher cellulase and endoglucanase activities (6.5 and 5.8 U/g) than those obtained using T. asperellum (5.6 and 4.1 U/g) with paper as substrate. There were no significant differences between isolates when grown on sawdust. It was possible to verify that native T. asperellum was able to produce cellulases on lignocellulosic material such as moistened paper and sawdust without having undergone a chemical pretreatment.